The Cognitive Crutch: A Systematic Literature Review of AI Dependency and The Decline in Critical Appraisal Skills Among Generation Z Students - Nurfauziah; Indra Sukma (Fakultas Teknik, Universitas Negeri Makassar, 2026)
Purpose – Growing concerns about the cognitive implications of generative AI overuse among Generation Z university students remain insufficiently addressed in the literature. This study examines the relationship between AI dependency and the decline in critical appraisal skills among Generation Z university students, responding to the absence of a systematic synthesis specifically targeting this demographic cohort. Methods – A Systematic Literature Review (SLR) was conducted across four databases Scopus, Web of Science, PubMed, using structured keywords related to generative AI, critical thinking, and Generation Z students. A total of 24 peer-reviewed international journal articles published between 2021 and 2025 met the inclusion criteria and were systematically analysed. Findings – Three major patterns were identified: (1) AI dependency reduces critical appraisal skills through cognitive offloading mechanisms, where students increasingly rely on AI generated responses rather than engaging in independent analysis; (2) Generation Z students demonstrated higher levels of AI dependency and lower critical thinking performance compared to older age groups; and (3) information literacy functions as a double edged moderator that may either mitigate or exacerbate the negative effects of AI dependency depending on students' evaluative abilities. Research implications – Findings are derived exclusively from peer-reviewed literature published between 2021 and 2025 and may not fully capture real-world classroom dynamics. Generalisability may be constrained by variability in how critical appraisal skills are operationalised and measured across the included studies, as well as the underrepresentation of non-Western educational contexts Originality – This is the first systematic review to synthesise empirical evidence linking AI dependency and critical appraisal skills exclusively among Generation Z students, integrating cognitive offloading theory, cognitive scaffolding, and digital cognitive atrophy into a unified analytical framework. Future research should examine longitudinal effects and test metacognitive scaffolding interventions across diverse educational contexts.